Proceedings of the 7th ACM International Conference on Bioinformatics, Computational Biology, and Health Informatics 2016
DOI: 10.1145/2975167.2975194
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Stochastic Model of the Budding Yeast Cell Cycle Control Mechanism

Abstract: The budding yeast cell cycle is regulated by a complex chemical reaction network. Several deterministic models have been proposed to model this control mechanism. However, experimental data exhibit considerable variability from cell to cell during cell growth and division. It is also observed that certain mutant cells are more vulnerable to noise than wild type cells. The observed variability comes from two sources: intrinsic noise coming from fluctuations of molecules and extrinsic noise introduced by variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For gene-mRNA-protein regulatory networks, an effective 'partitioning' strategy is to simulate mRNA synthesis and degradation by SSA and all subsequent protein-interaction processes by nonlinear ODEs. We have shown (Ahmadian et al, 2017;Liu et al, 2012;Wang et al, 2016) that this approach is 50-100 times faster than 'brute force' SSA, without sacrificing accuracy of the stochastic results.…”
Section: Stochastic Modelsmentioning
confidence: 95%
“…For gene-mRNA-protein regulatory networks, an effective 'partitioning' strategy is to simulate mRNA synthesis and degradation by SSA and all subsequent protein-interaction processes by nonlinear ODEs. We have shown (Ahmadian et al, 2017;Liu et al, 2012;Wang et al, 2016) that this approach is 50-100 times faster than 'brute force' SSA, without sacrificing accuracy of the stochastic results.…”
Section: Stochastic Modelsmentioning
confidence: 95%
“…After such partitioning we apply the HR hybrid algorithm to simulate the trajectories of state variables. The step by step algorithm is provided in [35,37] and more implementation details can be found in [42]. In those works, we have shown that placing the dynamics of mRNAs into SSA regime and solving ODEs for protein regulatory network leads to sufficiently accurate results, and significantly reduces the computational cost.…”
Section: The Hr Hybrid Modelmentioning
confidence: 99%
“…The main contribution of this paper is a new hybrid model that quantitatively describes key characteristics of the cell cycle, such as inter-division times and cell sizes, distribution of mRNAs, as well as the partial viability of specific mutant strains. Building on our previous work in [35], our new model includes the transcripts of the early G1 phase. This feature is in a direct contrast with existing works, such as [27, 35], that disregard the dynamics of early G1 proteins (Cln3 and Bck2) and do not include the G1 cyclin transcripts ( mCln3 and mBck2 ).…”
Section: Introductionmentioning
confidence: 99%